Influence of micro-patterned laser surface texturing on the tribological performance. (1st October 2007) - Wang, X.; Zhu, J.Y.; Chen, W.; Cai, L.
Laser Surface Texturing (LST) is an advanced method of surface micro-texturing technology. The aim of this paper is to investigate the effect of micro-patterned laser texturing surfaces on hydrodynamic lubrication. Numerical model of 3D micro-patterned laser texturing surfaces is set up based on Reynolds equation. By Full Multi-Grid (FMG) V Cycle Algorithm, matrix pattern and interfering pattern are investigated on several pattern parameters. It is shown that the lubrication performance is influenced by the type and parameter of the micro-pattern. Result indicates that the ability of interfering pattern on pressure built-up is better than the matrix pattern. It is clearly shown that the interfering ratio of interfering pattern also influences the lubricating performance and the optimal value of interfering ratio is around 0.4. Finally, geometry parameters of laser texturing micro-pore are also studied under patterned surface. Compared with previous literature in single micro-pore cell analysis, result shows that it is essential to investigate the geometry parameters of micro-pores in patterned surface. Numerical result of investigation has been applied in laser surface honing of cylinder-piston system successfully.